Best Practices in Academic Management. Study Programs Classification Model - Ofelia Ema Aleca; Florin Mihai (Amfiteatru Economic Journal, 2016)
This article proposes and tests a set of performance indicators for the assessment of Bachelor and Master studies, from two perspectives: the study programs and the disciplines. The academic performance at the level of a study program shall be calculated based on success and efficiency rates, and at discipline level, on the basis of rates of efficiency, success and absenteeism. This research proposes a model of classification of the study programs within a Bachelor and Master cycle based on the education performance and efficiency. What recommends this model as a best practice model in academic management is the possibility of grouping a study program or a discipline in a particular category of efficiency
Keywords: I250; 330; educational performance; educational efficiency; educational performance; indicators; curricula classification